Inhaled corticosteroid containing combinations and mortality in COPD. Issue 6 (13th December 2018) - Vestbo, Jørgen; Fabbri, Leonardo; Papi, Alberto; Petruzzelli, Stefano; Scuri, Mario; Guasconi, Alessandro; Vezzoli, Stefano; Singh, Dave
There is no solid evidence that any pharmacological treatment reduces mortality in chronic obstructive pulmonary disease (COPD). Two large trials with mortality as an efficacy outcome have been carried out testing a combination of a long-acting beta-agonist (LABA) and an inhaled corticosteroid (ICS) and in both, the reduction in mortality failed to reach statistical significance [1, 2]. This could be seen as proof of absence of effect, but given that the TORCH trial [1] resulted in a hazard ratio (HR) of 0.825 (95% CI 0.681–1.002; p=0.052) for the comparison of combined fluticasone propionate and salmeterol with placebo, the interpretation may not be that simple. The other negative trial, the SUMMIT trial [2], only included patients with moderate COPD and increased risk of cardiovascular comorbidity. Combinations containing inhaled corticosteroids may reduce mortality in patients with COPD http://ow.ly/6UCy30lpwEi